A convenient synthesis of 4-arylidene-2-phenyl-5(4H)-oxazolones under solvent-assisted grinding - Mookda Pattarawarapan (2018)
© 2016 Elsevier Ltd A facile and effective approach for the synthesis of 4-arylidene-2-phenyl-5(4H)-oxazolones has been developed. Under solvent-assisted grinding in the presence of 2,4,6-trichloro-1,3,5-triazine, catalytic triphenylphosphine, and sodium carbonate, dehydration–condensation of hippuric acid with aromatic aldehydes proceeded rapidly within minutes at room temperature to afford the products in good to excellent yields.